Literatur Review: The Role of Probiotics in Preventing Aging - Prima Minerva; Nur Indrawaty Lipoeto; Jamsari Jamsari; Tofrizal Tofrizal (GLOBAL HEALTH SCIENCE GROUP, 2026)
Aging is a complex biological process characterized by progressive functional decline of organs and tissues, largely driven by oxidative stress, chronic inflammation, and cellular senescence. Recent evidence suggests that age-related gut microbiota dysbiosis contributes significantly to inflammaging and oxidative damage, accelerating the aging process. Probiotics have emerged as potential gerobiotics due to their antioxidant, anti-inflammatory, and microbiota-modulating properties. This literature review aims to evaluate the role of probiotics in preventing and delaying the aging process through modulation of gut microbiota, oxidative stress reduction, and regulation of inflammatory. A narrative literature review was conducted using scientific publications from 2012 to 2023 obtained from NCBI (PubMed), ScienceDirect, and Google Scholar databases. Articles were selected based on relevance to probiotics, gut microbiota, oxidative stress, inflammation, and aging mechanisms. A total of 300 articles were identified from PubMed (n = 120), Science Direct (n = 95), and Google Scholar (n = 85). After removing duplicates, 235 articles were screened. 45 full text articles were assessed for eligibility, and 11 studies were included in the quantitative synthesis. The reviewed studies indicate that probiotics, particularly strains from the genera Lactobacillus, exert anti-aging effects by reducing reactive oxygen species (ROS), enhancing endogenous antioxidant enzymes (SOD, CAT, GPx), regulating inflammatory pathways (NF-κB, cytokines), activating Nrf2 signaling, maintaining intestinal barrier integrity, and restoring gut microbiota balance. Several probiotic strains were shown to delay telomere shortening, suppress cellular senescence markers, and improve metabolic. Probiotics play a significant role in preventing aging by modulating gut microbiota composition, reducing oxidative stress, and suppressing chronic inflammation. These findings support the potential application of probiotics as gerobiotics to promote healthy aging and extend health span.